Cloning, expression, purification and drug targeting of Plasmodium falciparum hypoxanthine guanine xanthine phosphoribosyltransferase (HGXPRT) - Mbewe, Boniface (Division of Chemical Pathology, 2014)
Includes bibliographical references.